Report on the seminar: An investigation of Calvin" s principles of Biblical interpretation - Armstrong, B. G. (Hervormde teologiese studies, 1998)
This article serves as a report on the seminar on 'Calvin the Preacher', held at the University of Pretoria during the Fifth South-African Congres of Calvin Research. In the seminar, where various examples of Calvin's interpretation were discussed, the basic principles of Calvin's method were enumerated. Although the discussions ranged far and wide, a valuable insight was gained in Calvin's methods. At the same time it became clear that Calvin's principles of Biblical interpretation had to receive more attention.